The moon as a symbol of death in "The Romance of the Moon, Moon" - William Leonardo Perdomo Vanegas (Corporación Universitaria Minuto de Dios, 2008)
The following article is an approach to semiotic analysis of the artistic text, specifically the poem. It takes up the thesis that consider poetic language as an integral element of semiotics, not linguistics. From a semiotic perspective, the text discusses the symbol of death in the Ballad of the Moon, Moon by Federico García Lorca, the analysis establishes a relationship between natural language and poetic language, reflecting part of Gypsy culture.